Analisis mengenai dampak lingkungan (AMDAL) sebagai upaya pencegahan pencemaran dan kerusakan terhadap lingkungan - Rahmadina, Rahmadina (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2025)
This research discusses environmental impact analysis (AMDAL) as an effort to prevent pollution and damage to the environment. Environmental problems are an undeniable issue both in Indonesia and in the world. Technological developments, the industrial world and population growth have an influence on environmental problems that affect the carrying capacity and capacity of the environment. Activities that have potential to damage the environment must require permits so that activities do not threaten the environment. This research aims to determine AMDAL as an effort to prevent pollution and damage to the environment. This type of research is a library method or library research, which is a form of activity relating to methods of collecting library data, reading and taking notes and processing research materials whether sourced from books, journals or statutory regulations.